A vision for restitution in Myanmar - Arraiza, J; Leckie, S (Refugee Studies Centre, University of Oxford, 2018)
People displaced in Myanmar during decades of civil conflict, as well as more recently displaced persons, need accessible legal pathways and assistance to regain access to their land and properties. Myanmar needs a clear vision on restitution to end its civil wars and displacement.